Potensi Rekayasa Kayu Pada Bangunan Green Architecture - I Putu Wikan Pithamaha; Cindy Avisha Khurniawan; I Made Pande Gosha Primayoga; Nyoman Ratih Prabandari; I Gede Surya Darmawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Environmental problems, notably global warming, have recently emerged as a source of concern. In the world of architecture, there is a phenomenon known as